The pesticides carbofuran and picloram alter the diversity and abundance of soil microbial communities - Alves Senabio, Jaqueline; Correia da Silva, Rafael; Guariz Pinheiro, Daniel [UNESP]; Gomes de Vasconcelos, Leonardo; Soares, Marcos Antônio (Public Library of Science (PLoS), 2024)
Many countries widely use pesticides to increase crop productivity in agriculture. However, their excessive and indiscriminate use contaminates soil and other environments and affects edaphic microbial communities. We aimed to examine how the pesticides carbofuran and picloram affect the structure and functionality of soil microbiota using cultivation-independent methods. Total DNA was extracted from microcosms (treated or not with pesticides) for amplification and metabarcoding sequencing for bacteria (16S gene) and fungi (28S gene) using Illumina-MiSeq platform. Data analysis resulted in 6,772,547 valid reads from the sequencing, including 3,450,815 amplicon sequences from the V3-V4 regions of the 16S gene and 3,321,732 sequences from the 28S gene. A total of 118 archaea, 6,931 bacteria, and 1,673 fungi taxonomic operating units were annotated with 97% identity in 24 soil samples. The most abundant phyla were Proteobacteria, Actinobacteria, Acidobacteria, Firmicutes, Chloroflexi, Euryarchaeaota, and Ascomycota. The pesticides reduced the diversity and richness and altered the composition of soil microbial communities and the ecological interactions among them. Picloram exerted the strongest influence. Metabarcoding data analysis from soil microorganisms identified metabolic functions involved in resistance and degradation of contaminants, such as glutathione S-transferase. The results provided evidence that carbofuran and picloram shaped the soil microbial community. Future investigations are required to unravel the mechanisms by which soil microorganisms degrade pesticides.